2019
DOI: 10.1177/0169796x19873744
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor in Farming Households in the Niger Delta Region of Nigeria

Abstract: Child labor is a major issue in many parts of the Global South. This study was conducted in the Niger Delta region of Nigeria to examine the level of involvement of children in arable farming activities. Three states in the region were selected for the study, and arable farming households were randomly selected from these states. Out of the selected farming households, 362 children (6–17 years of age) were interviewed. It was found that children were highly involved in most of the farming activities that are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The average of house hold size was five persons. Ofuoku, Ovharhe and Agbamu (2019) reported that most families in Delta State have an average of five to seven persons per household.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average of house hold size was five persons. Ofuoku, Ovharhe and Agbamu (2019) reported that most families in Delta State have an average of five to seven persons per household.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, youths have some level of farming experience due to child labour abuse, a situation where poor farm households pressurize children into farming activities in attept to make ends meet. This is socially unethical (Ofuoku, Ovharhe, and Agbamu, 2019).…”
Section: Test Of Hypothesis Onementioning
confidence: 99%
“…27 This perspective aligns with findings from other studies, which consistently show that child labour is more prevalent in economically disadvantaged communities. [27][28][29] A substantial majority (65.0%) of respondents in the urban group believed that child labour should be abolished in contrast with rural respondents where only 28.0% shared this viewpoint, while a considerable 65.5% remained undecided on the matter. This high proportion of undecided rural respondents may be indicative of the cultural acceptance of child labour as a means of supplementing family income in these areas.…”
Section: Facts and Figures By The Ilo Indicate That Childmentioning
confidence: 99%
“…Children could be considered successors in farming families (Rodriguez-Lizano, Montero-Vega, & Sibelet, 2020). As a farming family member, children play a role as labor-an essential input factor (Ofuoku, Ovharhe, & Agbamu, 2020;Sumberg & Sabates-Wheeler, 2020). Therefore, children or the younger generation are crucial in sustaining farming families.…”
Section: And Rural Development Researchmentioning
confidence: 99%